International Conference on Space Optics — ICSO 2018 2019
DOI: 10.1117/12.2536121
|View full text |Cite
|
Sign up to set email alerts
|

Optical feeder link architectures for very HTS: ground segment

Abstract: The paper deals with an analysis of Very High Throughput Satellite (VHTS) systems employing optical feeder links. As the capacities of newly announced next generation VHTS systems are exceeding the Terabit/s barrier, a large amount of investment needs to be directed not only to the space segment (as was the case traditionally), but also to the ground segment in support of the feeder links. To reduce this investment, satellite operators are reviewing various options and technologies for the feeder links, among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…The number and location of optical feeder stations are no longer constrained by considerations on frequency re-use or regulation issues but only on climatic conditions. Several studies have shown that a dozen stations in Europe (preferably in the south) can feed a VHTS in the 500-Gbps class with the required availability [2], [3]. As the satellite is accessed by a single station, all the traffic must be routed to the active station and the diversity network must be sized accordingly and consequently will be more expensive.…”
Section: How To Increase the Capacity Of The Feeder Linksmentioning
confidence: 99%
“…The number and location of optical feeder stations are no longer constrained by considerations on frequency re-use or regulation issues but only on climatic conditions. Several studies have shown that a dozen stations in Europe (preferably in the south) can feed a VHTS in the 500-Gbps class with the required availability [2], [3]. As the satellite is accessed by a single station, all the traffic must be routed to the active station and the diversity network must be sized accordingly and consequently will be more expensive.…”
Section: How To Increase the Capacity Of The Feeder Linksmentioning
confidence: 99%
“…Several papers have studied gateway diversity towards the optimization of High-Throughput Satellite (HTS) architectures. These works typically aim at optimizing the smart gateway configuration [33], gateway assignment [32], paving the way towards optical feeder links and dealing with atmospheric turbulence [34].…”
Section: Related Workmentioning
confidence: 99%
“…With such an approach, the authors in [23] have previously used the algorithm mentioned in theorem 3, for SDN controller placement at edge. In a similar fashion, let Vg be the maximum of equation (34). Thus, minimizing (34) is tantamount to maximizing…”
Section: Optimal Gateway Placementmentioning
confidence: 99%
“…Several studies have addressed this problem and have calculated the required number of OGSs for achieving a very high availability, either based on pure probability analysis or based on actual cloud coverage databases. A companion paper in the ICSO 2018 [5] is presenting a relevant analysis using a comprehensive generative tool developed under ESA INFRA "Optical/RF Tool," contract [6].…”
Section: Number Of Optical Ground Stations For Cloud Free Losmentioning
confidence: 99%
“…The paper highlights a number of technical issues that arise when adopting a particular optical feeder link architecture, and proposes key areas of R&D that need to be considered by the optical communications community. It does not address the topic of cloud blockage and on-ground spatial diversity (dealt with in a companion paper [5]), assuming that the number of optical ground stations is sufficient to guarantee the target feeder link availability.…”
Section: Introductionmentioning
confidence: 99%